2-Anilino-4-(1-methyl-1H-pyrazol-4-yl)pyrimidine-derived CDK2 inhibitors as anticancer agents: Design, synthesis & evaluation. (15th February 2023) - Fanta, Biruk Sintayehu; Mekonnen, Laychiluh; Basnet, Sunita K.C.; Teo, Theodosia; Lenjisa, Jimma; Khair, Nishat Z.; Kou, Lianmeng; Tadesse, Solomon; Sykes, Matthew J.; Yu, Mingfeng; Wang, Shudong
Graphical abstract: Abstract: Deregulation of cyclin-dependent kinase 2 (CDK2) and its activating partners, cyclins A and E, is associated with the pathogenesis of a myriad of human cancers and with resistance to anticancer drugs including CDK4/6 inhibitors. Thus, CDK2 has become an attractive target for the development of new anticancer therapies and for the amelioration of the resistance to CDK4/6 inhibitors. Bioisosteric replacement of the thiazole moiety of CDKI-73, a clinically trialled CDK inhibitor, by a pyrazole group afforded 9 and 19 that displayed potent CDK2-cyclin E inhibition ( K i = 0.023 and 0.001 μM, respectively) with submicromolar antiproliferative activity against a panel of cancer cell lines (GI50 = 0.025–0.780 μM). Mechanistic studies on 19 with HCT-116 colorectal cancer cells revealed that the compound reduced the phosphorylation of retinoblastoma at Ser807/811, arrested the cells at the G2/M phase, and induced apoptosis. These results highlight the potential of the 2-anilino-4-(1-methyl-1 H -pyrazol-4-yl)pyrimidine series in developing potent and selective CDK2 inhibitors to combat cancer.